Penyelesaian Tindak Pidana Penganiayaan di Wilayah Hukum Kepolisian Sektor Pasar Jambi (Studi LP No: B/32/X/2021/Polsek Pasar Jambi/Polresta Jambi/Polda Jambi) - M. Rudi Hartono; Karina Karina (Wajah Hukum, 2022)
The act of persecution is a prohibited act and this is not justified according to the Criminal Code as regulated in Article 351 of the Criminal Code. Persecution is an act that is intended to cause pain or injury to another person, the perpetrator intends to cause pain or torture as a result of the act such as hitting, kicking, kicking, scratching and others. This study aims to obtain a more in-depth picture of the factors causing the occurrence of criminal acts of persecution that occurred in the jurisdiction of the Jambi market sector police department, Jambi City with Police Report Study No: B/32/X/2021/Polsek Pasar Jambi/Polresta Jambi/Polda Jambi, efforts to resolve criminal acts and obstacles found in the process of resolving criminal acts of persecution. The method used in this study is an empirical research method with the type of case study research. The subjects in this study were 1 head of crime department, 1 investigator, 1 perpetrator, and 1 victim. Data collection methods in this study used interviews and observation. The conclusion in this thesis is that the persecution that occurred in the Jambi Market Police Sector Law was influenced by the factor that the perpetrator felt annoyed and angry with his girlfriend and his ego was too high, so that the perpetrator carried out the abuse. The process of resolving the persecution case in the Jambi Market Police Sector Legal Area is carried out through an investigation, by asking for information between the perpetrator and the victim, because this problem is a complaint offense, meaning that this case can be stopped and withdrawn by the reporting party and peaceful.